ANALYZING APPROACH SELECTIONS IN 99-ENDING PRICES AND THEIR IMPACT ON PURCHASE INTENTION IN THE INDONESIAN MARKET - Ananda, Indhy Agustya; Haryanto, Jony Oktavian (IDEAS: Journal of Management & Technology, 2025)
This research seeks to find the relation from 99 marketing techniques in purchase intention for Indonesian market, how visualization with typographic and color brightness impact purchase intention Using a mixed-method approach, quantitative data from surveys combined with qualitative insights from post-survey interviews. The findings have significant implications for marketers and retailers aiming to enhance pricing strategies within Indonesia's evolving retail environment. The results show that 99-ending prices had a secondary beneficial influence on people's perception of their affordability and bright colors, and low curvature typefaces were shown to be the most practiced visual combinations. The research also exposes practical realities, including an in-built need for prices like Rp19,900 to fit in with local payment practices and cultural norms. Although the strategy is broadly effective, its impact differs by demographic group, highlighting the importance of targeted approaches.